PENYULUHAN PEMANFAATAN JUS BUAH BIT UNTUK MENINGKATKAN KADAR HB REMAJA - Husna Sari; Elvida Sulistiani; G.F Gustina Siregar; Ilvira Ulpa Ismail; Peny Ariani; Tifani Hadi Tri wahyuni (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Anemia is a condition of decreased levels of red blood cells in the body. A y oung woman is said to be anemic when her Hb content is less than 12 gr/dl (Masriadi, 2018). Some of the symptoms of anemia are easily tired, lack of energy in activities and reduce the enthusiasm for learning in adolescents. Adolescent girls are prone to anemia because teenage girls experience menstruation, which is a process where the uterine wall is injured so that sufficient hemoglobin levels are needed, especially in women. According to Riskedas data in 2018, female adolescents experienced anemia, namely 48.9%, with the proportion of anemia in the age group 15-24 years (Health, 2018). Anemia can be treated with pharmacological and non-pharmacological methods. Tablets (Fe) are used in pharmacological treatment and one of the non-pharmacological therapies used to increase Hb levels is beets. Chemical compounds and vitamins in beets are known to be able to increase Hb levels in adolescents. This PKM activity with the counseling method aims to provide information to teenagers about the use of beetroot juice in increasing Hb levels in adolescents. The process of implementing this community service activity is carried out by providing information and education to teenagers regarding anemia, the content of beets and how to process them so that they can become a drink that can increase adolescent Hb levels. Then the adolescents were distributed pre-test and post-test questionnaires to the participants and the results were obtained as much as 63% of the 35 adolescents had an increase in adolescent knowledge of how to prevent anemia with non-pharmacological therapy, namely beetroot juice.